Comparison and optimization of sheep in vivo intervertebral disc injury model. Issue 2 (22nd April 2022) - Constant, Caroline; Hom, Warren W.; Nehrbass, Dirk; Carmel, Eric‐Norman; Albers, Christoph E.; Deml, Moritz C.; Gehweiler, Dominic; Lee, Yunsoo; Hecht, Andrew; Grad, Sibylle; Iatridis, James C.; Zeiter, Stephan
Abstract: Background: The current standard of care for intervertebral disc (IVD) herniation, surgical discectomy, does not repair annulus fibrosus (AF) defects, which is partly due to the lack of effective methods to do so and is why new repair strategies are widely investigated and tested preclinically. There is a need to develop a standardized IVD injury model in large animals to enable comparison and interpretation across preclinical study results. The purpose of this study was to compare in vivo IVD injury models in sheep to determine which annulus fibrosus (AF) defect type combined with partial nucleus pulposus (NP) removal would better mimic degenerative human spinal pathologies. Methods: Six skeletally mature sheep were randomly assigned to one of the two observation periods (1 and 3 months) and underwent creation of 3 different AF defect types (slit, cruciate, and box‐cut AF defects) in conjunction with 0.1 g NP removal in three lumbar levels using a lateral retroperitoneal surgical approach. The spine was monitored by clinical CT scans pre‐ and postoperatively, at 2 weeks and euthanasia, and by magnetic resonance imaging (MRI) and histology after euthanasia to determine the severity of degeneration (disc height loss, Pfirrmann grading, semiquantitative histopathology grading). Results: All AF defects led to significant degenerative changes detectable on CT and MR images, produced bulging of disc tissue without disc herniation and led to degenerative and inflammatory histopathological changes. However, AF defects were not equal in terms of disc height loss at 3 months postoperatively; the cruciate and box‐cut AF defects showed significantly decreased disc height compared to their preoperative height, with the box‐cut defect creating the greatest disc height loss, while the slit AF defect showed restoration of normal preoperative disc height. Conclusions: The tested IVD injury models do not all generate comparable disc degeneration but can be considered suitable IVD injury models to investigate new treatments. Results of the current study clearly indicate that slit AF defect should be avoided if disc height is used as one of the main outcomes; additional confirmatory studies may be warranted to generalize this finding. Abstract :